2004
DOI: 10.1892/0891-6640(2004)18<52:teoeou>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise on Urinary Albumin Excretion in Dogs

Abstract: Persistent microalbuminuria has been shown to be an indicator of glomerular damage associated with early progressive renal disease in people and dogs. In people, transient or reversible microalbuminuria has been shown to occur with exercise. A semi-quantitative test to measure microalbuminuria in the dog recently has become available. The purpose of this study was to determine if mild-to-moderate exercise induced microalbuminuria in the dog. Twenty-six dogs were included in the study after undergoing tests to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
(35 reference statements)
1
14
1
1
Order By: Relevance
“…It has been established that both short maximal and submaximal exercises cause significant increases in TPP because a shift of fluids from the vascular compartment to the extracellular fluid spaces (Ilkiw et al, 1989;Rovira et al, 2007a). On the contrary, TPP decreased during prolonged exercise in dogs because of increased plasma volume, exercise-induced immunosuppression, catabolism of plasma proteins for energy and protein loss via renal and gastrointestinal tracts (Hinchcliff et al, 1998;Gary et al, 2004;McKenzie et al, 2007). On the other hand, plasma CREAT concentrations increased significantly with E and remained elevated throughout the recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that both short maximal and submaximal exercises cause significant increases in TPP because a shift of fluids from the vascular compartment to the extracellular fluid spaces (Ilkiw et al, 1989;Rovira et al, 2007a). On the contrary, TPP decreased during prolonged exercise in dogs because of increased plasma volume, exercise-induced immunosuppression, catabolism of plasma proteins for energy and protein loss via renal and gastrointestinal tracts (Hinchcliff et al, 1998;Gary et al, 2004;McKenzie et al, 2007). On the other hand, plasma CREAT concentrations increased significantly with E and remained elevated throughout the recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cutoff value of >10 mg/L albumin, the ERD test strips had a sensitivity and specificity of 91% and 92%, respectively, for the detection of microalbuminuria, with a false‐negative rate of 9% and a false‐positive rate of 8%. In a recent study, it was reported that 19% of clinically healthy dogs had microalbuminuria (albumin between 10 and 300 mg/L) and 2% had overt proteinuria (albumin >300 mg/L) 16 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COX-2 is sparsely expressed in the macula densa of the normal dog kidney, and up-regulation of COX-2 in the kidney and the stomach [16] has also been reported by several studies in dogs with volume or salt depletion; these results suggest that COX-2 and COX-1 have a possible role in the response that helps maintain renal function [3,22,40]. Thus, it is thought that ketoprofen inhibits mainly COX-1 in the kidney and that prednisolone may concomitantly block up-regulation of COX-2 that helps maintain renal function, which results in a decrease of RPF and GFR and causes the renal tubular injuries and hyperalbuminuria, which are early marker of renal disease in dogs [12,13,25]. On the other hand, fairly abnormal enzymuria with exfoliation of RTE cells in the urine was observed, although meloxicam co-administered with prednisolone showed no other significant changes in renal function and albuminuria compared with the negative control group and the pretreatment values.…”
Section: Disccusionmentioning
confidence: 87%